2020
DOI: 10.1177/0022034520962751
|View full text |Cite
|
Sign up to set email alerts
|

Dental Research Waste in Design, Analysis, and Reporting: A Scoping Review

Abstract: Research waste is highly prevalent across biomedical investigations. We aimed to assess the evidence on the extent of research waste in dental research. We performed a scoping review of empirical evaluations of dental studies assessing the prevalence and impact of limitations in design, conduct, analysis, and reporting of research. PubMed was searched using specific terms to retrieve studies dealing with design, conduct, analysis, and reporting of studies in dentistry, with no year or language restrictions. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
2
21
1
1
Order By: Relevance
“…The greatest number of trials was published in 2019 (33.3%) and in orthodontic specialty journals (61.9 %). The median number of time points was four (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Approximately 90% of the studies reported a 1:1 treatment arm allocation ratio.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The greatest number of trials was published in 2019 (33.3%) and in orthodontic specialty journals (61.9 %). The median number of time points was four (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Approximately 90% of the studies reported a 1:1 treatment arm allocation ratio.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] The importance of trials having an appropriate sample size is further highlighted by the fact that overestimation of the calculated required sample size can lead to additional study costs, resource waste, and potentially result in participants being exposed to ineffective/harmful treatments. 5,6 Alternatively, underestimation of the sample size can result in small trials that are considered less reliable and likely to report equivocal results attributed to a lack of study power to detect differences between intervention groups. 7,8 To understand the effect of interventions over time within the same individual, longitudinal orthodontic trials involving the repeated measurement of outcomes over several time points are commonly conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been used to study this relationship, which range from in vitro experiments to animal, epidemiological, and clinical studies. A recent study prompted our interest in highlighting some of the methodological gaps of epidemiological studies that investigate the relationship between oral and systemic diseases (Pandis et al 2020). For example, the authors of many reviews in this area conclude that studies are of poor quality (Simpson et al 2015; Liu et al 2019; Manohar et al 2020), yet there are no articles that attempt to address the common concerns raised in these studies.…”
mentioning
confidence: 99%
“…This is often due to an overreliance on an arbitrary 0.05 threshold or use of statistical methods that produce “statistically significant” results (Greenland et al 2016). Reporting, focusing, and highlighting P values is an endemic practice across medical and dental fields (Greenland et al 2016; Pandis et al 2020). For instance, a review on obesity and periodontal disease reported 15 single P values without corresponding estimates on effect size in a single paragraph (Martens et al 2017).…”
mentioning
confidence: 99%